Diccionario de sinónimos de la lengua achuar para estudiantes de EGB - Senkuam Wisui, Tseremp Ernesto (2018)
For the elaboration of this material the investigation was developed in two communities Mashumarentsa and Juyukamentsa. The work has the fundamental parts: first reference is made to some theoretical questions about the sign-object relationship; some sources were reviewed and analyzed, in accordance with the proposed topic. In the methodology, three instruments were applied to gather the information; the interview was conducted through the family visit to the elderly, the questions were asked verbally here. In the field of observation, the elderly, children and young people who use their language, with a search of data, made a dictionary in alphabetical order of the synonym words Achuar, used in the language. of students of basic general education, and family kinship. Through this investigative work, we got to know the news in our language, there are changes of terms, new synonymous words have been created according to the current life. And the difference between Achuar and Castilian was also found, because in Achuar there are few substantive words that are recognized as synonyms, however, there are many in Spanish. Likewise, in adjectives there are few words that we recognize as synonyms, that is, they can be said in different ways, in verbs there are more synonyms.